Geopolitics, Aid, and Growth : The Impact of UN Security Council Membership on the Effectiveness of Aid - Dreher, Axel; Eichenauer, Vera Z.; Gehring, Kai (World Bank, Washington, DC, 2016)
The paper investigates the effects of short-term political motivations on the effectiveness of foreign aid. Specifically, the paper tests whether the effect of aid on economic growth is reduced by the share of years a country served on the United Nations Security Council (UNSC) in the period the aid is committed, which provides quasi-random variation in aid. The results show that the effect of aid on growth is significantly lower when aid was committed during a country's tenure on the UNSC. This holds when we restrict the sample to Africa, which follows the strictest norm of rotation on the UNSC and thus where UNSC membership can most reliably be regarded as exogenous. Two conclusions arise from this. First, short-term political favoritism reduces the effectiveness of aid. Second, results of studies using political interest variables as instruments for overall aid arguably estimate the effect of politically motivated aid and thus a lower bound for the effect of all aid.